The effectiveness of different density signal stimuli perception from different distances - Penkauskas, A. (Psichologija, 1965)
The Article analyzes the effectiveness of different density signal stimuli perception from different distances. The study found that by varying the density of signal stimuli the optimal perception distance is 2-4 meters.